Genotype-phenotype correlations of STXBP1 pathogenic variants and the treatment choices for STXBP1-related disorders in China - Miriam Kessi; Baiyu Chen; Li-Dan Shan; Ying Wang; Lifen Yang; Fei Yin; Fang He; Jing Peng; Guoli Wang (BMC, 2023)
Abstract Background We aimed to analyze the genotype-phenotype correlations of STXBP1 pathogenic variants, prognostic factors and the treatment choices in a case-series of STXBP1-related disorders from China. Methods The clinical data and genetic results of the children diagnosed with STXBP1-related disorders at Xiangya hospital from 2011 to 2019 were collected retrospectively, and analyzed. We divided our patients into groups for comparison purposes: patients with missense variants and nonsense variants, patients who are seizure-free and not seizure-free, patients with mild to moderate intellectual disability (ID) and severe to profound global developmental delay (GDD). Results Nineteen patients were enrolled: 17 (89.5%) unrelated and 2 (10.5%) familial. Twelve (63.2%) were females. Developmental epileptic encephalopathy (DEE) was observed in 18 (94.7%) patients and ID alone in 1 (5.3%) individual. Thirteen patients (68.4%) had profound ID/GDD, 4 (23.53%) severe, 1 (5.9%) moderate and 1 (5.9%) mild. Three patients (15.8%) with profound ID died. A total of 19 variants were detected: pathogenic (n = 15) and likely pathogenic (n = 4). Seven were novel variants: c.664-1G>-, M486R, H245N, H498Pfs*44, L41R, L410del, and D90H. Of the 8 previous reported variants, 2 were recurrent: R406C and R292C. Anti-seizure medications were used in combinations, and 7 patients became seizure-free, and most of them achieved seizure freedom within the first 2 years of life irrespective of the type of the mutation. Effective medications for the seizure-free individuals included adrenocorticotropic (ACTH) and/or levetiracetam and/or phenobarbital and/or sodium valproate and/or topiramate and/or vigabatrin and/or nitrazepam. There was no correlation between the types of pathogenic variants and the phenotypes. Conclusion Our case-series showed that there is no genotype-phenotype correlation in patients with STXBP1-related disorders. This study adds 7 novel variants which expand the spectrum of STXBP1-related disorders. Combinations of levetiracetam and/or sodium valproate and/or ACTH and/or phenobarbital and/or vigabatrin and/or topiramate and/or nitrazepam were more often associated with seizure freedom in our cohort within 2 years of life.